'Wading through treacle': quality improvement lessons from the frontline. Issue 3 (23rd December 2011) - Roueche, Alice; Hewitt, Jocelyn
Abstract : In a time of financial uncertainty and structural reform, the National Health Service (NHS) in England needs clinical leadership to help improve the quality of patient care. Increasingly, leadership development is being targeted at doctors in postgraduate training to help prepare them for their future leadership roles as consultants and general practitioners. However, there is a risk that we are missing an opportunity here by failing to recognise the role that doctors in training can play now, during their training. As our frontline clinicians they have a unique view of the health service and the inefficiencies therein. The London Deanery has been running an educational programme called Beyond Audit to provide doctors in training with quality improvement skills. During this programme we have been given a unique insight into NHS systems as viewed by junior doctors. They have identified a wide range of small system problems that, when combined, result in large-scale inefficiency and prevent the delivery of high quality patient care. These problems they identify have implications for cost, efficiency, patient safety, team-working and patient experience. Any attempt to improve the quality of care delivered in the NHS needs to look at the system from the point of view of those delivering the care, including our doctors in postgraduate training. By empowering them to make improvements to the systems that they see, there is the potential to make significant improvement in the quality of patient care that they deliver.